“Somos um país de jovens”: a cultura das políticas da ditadura militar brasileira para a juventude - Gabriel Amato Bruno de Lima (2023)
This thesis’ theme is the youth policies of the Brazilian military dictatorship created between 1967-68 and composed by the Rondon Project, the Mauá Operation and the youth directories of the political parties (the Aliança Renovadora Nacional – Arena and the Movimento Democrático Brasileiro – MDB). From an epistemological dialogue between political history and the interpretative current of Anthropology, I study the culture (in an anthropological sense) of these policies. My approach, in this sense, focuses on the analysis of the codes and cultural norms that support both these dictatorial programs aimed at the youth and the political behaviors – of young people and non-young people – that occurred in the spaces delimited by these state policies. I argue that culture constituted a central element for behaviors of approximation and conflict with the regime, thus configuring complex intersections between youths and dictatorship during the 1960s and 70s. In this sense, I analyze a wide range of historical sources in different typologies (journalistic, official, imagery, police etc.) as cultural data in order to interpret the “native points of view” about these programs. The thesis is divided into three parts, all with two chapters each. In the first, I analyze the context of transnational emergence of youth as a disruptive political subject in the late 1960s, as well as the structuring of state policies addressed to youth that, in dictatorial Brazil, took place as a response to the recognition of youth as a condition, by itself, qualified for power struggles. In the second part, I analyze youth political action in these programs created by the regime bearing in mind both the “prescribed” and the “performative” dimensions of a cultural category of political behavior created in this context: participação, which sought to configure itself as an alternative to leftist youth engajamento. Finally, in the third part, I analyze youth itself as a cultural category elaborated and re-elaborated in the context of the Brazilian dictatorship, first from the reflection on the attempts to establish precise boundaries for the youth condition within the scope of state programs and, former, analyzing differences of gender and class that emerged in the experience of the youth that took part on these policies. I conclude, therefore, that the realization that “we are a country of young people” generated government actions aimed at youth that kept cultural and political specificities associated with the context of dictatorial Brazil.